Scrub typhus meningoencephalitis in children: A single centre, observational study from Eastern India - Preetinanda Parida; Aman Kumar Agrawal; Sebaranjan Biswal; Sibabratta Patnaik; Chinmay Kumar Behera (Wolters Kluwer Medknow Publications, 2021)
Background: Scrub typhus is being reported from different parts of India. Meningitis or meningoencephalitis among various neurological complication seen in scrub typhus is not uncommon. Delay in diagnosis may cause higher mortality without prompt treatment. The aim of the study was to describe the various manifestations of scrub typhus meningoencephalitis and their outcome from eastern part of India. Subjects and Methods: A prospective observational study of scrub meningoencephalitis was carried out at Kalinga Institute of Medical Sciences, between October 2018 and August 2020.The diagnosis was made based on the compatible clinical features, positive Scrub Ig M by ELISA and cerebrospinal fluid lymphocytosis (>5 cell/cmm), after excluding other causes of meningoencephalitis. Results: Twenty-seven (12.38%) cases of scrub meningoencephalitis were included in the study with male (66.6%) predominance. All had presented with fever of mean duration of 8.5 days of illness. Altered sensorium and seizure was observed in 70.5% and 62.9% of our patients along with two patients who had sixth cranial nerve palsy. Eschar was found in 25.9% of our children. The mean CSF cell count, protein and glucose were 25 cells/cmm,84.2 mg/dL and 62.9 mg/dL respectively with lymphocytosis in all cases. There was no mortality in this study. Conclusion: Meningoencephalitis is an important complication of scrub typhus in children. Unlike most viral encephalitis cases, it has a definite treatment with good outcome, if treated early.